METHODICAL APPROACHES TO COLLECTING AND ANALYZING THE EXHALED BREATH CONDENSATE - Ya.M. Avramenko; O.A. Borzykh (Проблеми екології та медицини)
Currently, one of the promising non-invasive diagnostic methods in pulmonology, cardiology, endocrinology, oncology is the study of the exhaled breath condensate (EBC). A significant limitation of the study of EBC in clinical practice is the absence of generally accepted standards for its collection and study of the content of biological substances containing ultra low concentrations in it. The growing scientific and practical interest in this issue led to the organization of the target group American Thoracic Society and the European Respiratory Society and the development of recommendations for the collection of condensate. We have studied and analyzed the recommendations of ATS / ERS and developed an algorithm for sampling EBC.